DETERMINAN KEJADIAN STUNTING PADA ANAK USIA 6-23 BULAN DI KABUPATEN DEMAK - Dinata, Budi Wahyu; Mintarsih, Sri Noor; Sulistyowati, Enik (Poltekkes Kemenkes Semarang, 2018)
Background : Stunting is a linear growth disorder in which a short or very short body condition that occurs due to malnutrition and recurrent disease over a long period of time during the fetus for the first 2 years. The factors that influence stunting are the level of energy, and protein adequacy, breastfeeding, administration of IMD, and administration of vitamin A. Objective: To determine the relationship between energy adequacy, protein adequacy, breastfeeding, initiation of early breastfeeding, and vitamin A capsule administration with the incidence of stunting in children aged 6-23 months in Demak Regency. Method: This type of research is an observational study with a cross sectional design. This study uses secondary data from surveys of nutritional status assessment and monitoring of nutritional consumption carried out in 2017. The data collected was the level of energy, and protein adequacy, breastfeeding, administration of IMD, and vitamin A administration for children under five were toddlers aged 6-23 months in Demak Regency. The results of the analysis used descriptive analysis with numerical and categorical data, and analytical analysis using multivariate analysis with multiple logistic regression test. Results: The results of multivariate analysis showed that the level of energy sufficiency lacked risk of 3,756 stunting, the level of protein sufficiency lacked a risk of 4,781 times stunting, non-exclusive breastfeeding had a stunting risk of 2,054, adherence was not done and IMD had a risk of 2,708 times stunting, and not given vitamin A tablets have a risk of 23.5 times stunting. The overall analysis of the variables carried out with the results that giving vitamin A had the most dominant results was 23.5 times the incidence of stunting.Conclusion: The results of the analysis get the overall results of the variables at risk of stunting. However, the dominant variable in stunting in infants is giving vitamin A capsules